2020
DOI: 10.1103/physrevd.101.034508
|View full text |Cite
|
Sign up to set email alerts
|

θ -dependence and center symmetry in Yang-Mills theories

Abstract: We investigate the relation between the realization of center symmetry and the dependence on the topological parameter θ in SU (N ) Yang-Mills theories, exploiting trace deformations as a tool to regulate center symmetry breaking in a theory with a small compactified direction. We consider, in particular, SU (4) gauge theory, which admits two possible independent deformations, and study, as a first step, its phase diagram in the deformation plane for two values of the inverse compactified radius going up to L … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 120 publications
1
17
0
Order By: Relevance
“…[174]. A number of results at varying N c at finite-temperature exist 19 [64,82,84,[175][176][177][178][179][180][181][182][183][184]. Recent lattice results with different gauge groups and fermion content can be found in [114,[185][186][187].…”
Section: Discussionmentioning
confidence: 99%
“…[174]. A number of results at varying N c at finite-temperature exist 19 [64,82,84,[175][176][177][178][179][180][181][182][183][184]. Recent lattice results with different gauge groups and fermion content can be found in [114,[185][186][187].…”
Section: Discussionmentioning
confidence: 99%
“…Analytic estimates ofχ and of theb 2n coefficients are available only for two dimensional models [9][10][11][12][13]. Given the non-perturbative nature of θ-dependence, the numerical lattice approach is the natural tool to investigate such topics quantitatively, and in particular to test large-N predictions [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. There are however some non-trivial computational challenges that have to be faced, especially in the large N regime.…”
Section: Jhep03(2021)111mentioning
confidence: 99%
“…The method was exploited for the determination of the b 2n coefficients first in ref. [22] and later developed and applied in several works to both SU(N ) Yang-Mills theory [13,[25][26][27] and two dimensional CP N −1 models [37,38].…”
Section: Jhep03(2021)111mentioning
confidence: 99%
“…Unquestionably, as the parameter h is switched on, both quantities approach the zero-temperature values. Furthermore, a study in SU(4) has shown that the θ -dependence of the deformed theory coincides with that at zero temperature whenever there is full center symmetry restoration [35,36].…”
Section: Pos(lattice2019)276mentioning
confidence: 99%